How customer and brand orientation influence brand evangelism in university? - Mazuri, Abd Ghani; Zulqurnain, Wan Ismail; Rashidah, Mohamad Ibrahim (2016)
The increasingly competitive environment being experienced by all sector has led to brands being increasingly used as a strategic resource to achieve a competitive advantage. This has led to an extensive research on brand orientation as a possible approach to govern the brand building process within organizations. Many managers today recognize that the ability to succeed in the marketplace requires more than just sales technique. Hence, business and service organizations including higher education institutions seek to achieve a competitive advantage in their dynamic environments by being customer and brand driven. Undoubtedly, every university needs a brand that can be trusted and that will differentiate it from others. Therefore, the main objective of this study is to examine the influence of customer orientation and brand orientation on brand evangelism among students. A sample of 118 undergraduate students was collected via survey questionnaire. The collected data were analyzed using SPSS and Partial Least Squares 2.0 (PLS2) which empirically support that customer orientation and brand orientation positively effect on brand evangelism among students in university.